Adherence to Guidelines in Postpartum Management of Hypertensive Disorders in Pregnancy in Tertiary Health Facilities in Nigeria: A Multi-centre Study. Issue 1 (1st January 2021) - Oyeneyin, Lawal; Ishaku, Salisu; Azubuike, Onyebuchi; Agbo, Innocent; Dattijo, Lamaran; Baffah, Aminu; Kayode, Gbenga; Owa, Olorunfemi; Odusolu, Patience; Tunau, Karima; Tukur, Jamilu; Warren, Charlotte; et al.
ABSTRACT: Hypertensive disorders in pregnancy (HDPs) are a leading cause of maternal morbidity and mortality. Available guidelines for their postpartum management are expected to be optimally utilized. This study aimed to determine adherence to guidelines in selected Nigerian tertiary hospitals. It was nested in a cohort of women with HDPs who delivered in eight facilities between October 2017 and June 2018. Nine weeks after delivery, their cases were evaluated on prespecified indicators and supplemented with interviews. The level of adherence to the guidelines was determined using descriptive analyses, including frequencies, percentages, means, and standard deviations, as well as charts. Of the 366 participants, 33 (9%), 75 (20%), 200 (55%), and 58 (16%) had chronic hypertension, gestational hypertension, preeclampsia, and eclampsia, respectively. Only about a third had their blood pressure measured between postpartum days three and five. Similarly, a third of those with persistent hypertension (≥140/90 mmHg) were not on antihypertensive medications within the first week postpartum. In addition, 37% and 42% of participants were not counseled on contraceptives and early subsequent antenatal visits, respectively. Among those with preeclampsia/eclampsia, 93% were not offered postpartum screening for thromboprophylaxis. Although all women with preeclampsia/eclampsia remained hypertensive two weeks after discharge, only 24% had medical reviews. Overall, only 58% and 44% of indicators were adhered to among all HDPs and preeclampsia/eclampsia-specific indicators, respectively. Level of adherence to guidelines on postpartum management of HDPs in Nigerian tertiary hospitals is poor. It is recommended that institutionalization of guidelines be prioritized and linked to the entire continuum from preconception through longer term postpartum care.